Antibody Recognition of Fluorinated Haptens and Antigens - Reindl, Maximilian; Hoffmann-Roder, Anja (Current Topics in Medicinal Chemistry, 2014)
Regarding its many roles for lead optimization and drug development, fluorine will definitely continue to be of major importance in medicinal chemistry. With safe and selective fluorinating agents at hands, the use of fluorinated compounds has become routine in pharmaceutical and material sciences and many of the well-appreciated organofluorine inductive effects are now understood. In contrast, our knowledge of how fluorine affects binding affinity and selectivity of proteins and antibodies at the molecular level is by far less advanced. Thus, applications of fluorinated haptens and antigens in the mapping of binding epitopes for various antibodies of diagnostic and therapeutic relevance, as well as for the generation of immune modulating agents and ligands with enhanced T cell affinity are reviewed. Moreover, recent examples of vaccines against cocaine and cancer based on selectively fluorinated antigens with improved antigenic properties are presented.
Keywords: epitope mapping